2018
DOI: 10.4067/s0719-01072018000300143
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of color change using CIE LAB coordinates on tooth structure subjected to different concentrations of peroxide carbamide

Abstract: Aim:The aim of this study was to evaluate the optical behavior of tooth color using CIE L*A*B* space; the teeth were subjected to novel bleaching gels containing peroxide carbamide with potassium oxalate. Materials and Method: Three different carbamide peroxide gels were experimentally fabricated. They consisted of 10% (G10), 16% (G16) and 37% (G37) concentrations. Sixty recently extracted premolars were subjected to different bleaching protocols. Color change (ΔE) was assessed using the CIE L*a*b* system afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Another study has emphasized the effectiveness of carbamide peroxide in home bleaching, indicating its potential for discoloration based on a literature review [16]. Additionally, Durán et al ( 2018) have found that concentrations of 10% and 16% carbamide peroxide, when combined with potassium oxalate and uoride, were not associated with tooth sensitivity, suggesting that the 16% concentration might already be optimal without added bene ts [17].…”
Section: Discussionmentioning
confidence: 99%
“…Another study has emphasized the effectiveness of carbamide peroxide in home bleaching, indicating its potential for discoloration based on a literature review [16]. Additionally, Durán et al ( 2018) have found that concentrations of 10% and 16% carbamide peroxide, when combined with potassium oxalate and uoride, were not associated with tooth sensitivity, suggesting that the 16% concentration might already be optimal without added bene ts [17].…”
Section: Discussionmentioning
confidence: 99%
“…Variations also occurred 1 month after the end of the whitening treatment, with an increase in ΔE, indicating that the whitening process continued throughout the days following treatment. Durán et al (2018) [ 37 ] observed that this variation of ΔE tends to increase, due to the slow release of CP in the tooth and the stability of the tooth color. Tooth tissues, enamel, and dentin have distinct characteristics of opacity and translucency which are not monochromatic, but rather involve different colors in dispersion, requiring time to reach complete stability, justifying the increase in ΔE after completion of the whitening treatment in this study.…”
Section: Discussionmentioning
confidence: 99%